The influence of IOS, DER, and ROA on the value of transportation and logistics companies listed on the IDX in 2017-2021 - Nurfika Dewi; Defriko Gusma Putra; Indra Mulia Pratama (Universitas Pendidikan Nasional, 2022)
This research is motivated by the low average PBV of sector companies’ transportation and logistics compared to other sectors over the last 5 years. The aim of this research is to determine the influence of Investment Opportunity Set, Modal Structure, and Profitability on Sector Company Value Transportation and Logistics Listed on the Indonesian Stock Exchange 2017-2021 partially and simultaneously. The results of this research show that the investment Opportunity Set proved to have a significant negative effect on company value in the sector of transportation and logistics which is listed on the Indonesian stock exchange in 2017-2021. Based on the results of data analysis value statistics amounting to -2.811539 with a probability value of 0.0147 < 0.05. The capital structure is proven not to influence stomach values in the sector of transportation and logistics which is listed on the Indonesian stock exchange in 2017-2021. Based on the results of data analysis value statistics amounting to -0.337478 with a probability value of 0.7411 > 0.05. Proven profitability significant negative effect on company value in the sector of transportation and logistics which is listed on the Indonesian stock exchange in 2017-2021. Based on the results of data analysis obtained tstatistics of -2.326885 with a probability value of large 0.0368 < 0.05.